Development of new mutant alleles and markers for KTI1 and KTI3 via CRISPR/Cas9-mediated mutagenesis to reduce trypsin inhibitor content and activity in soybean seeds - Wang, Zhibo; Shea, Zachary; Rosso, Luciana; Shang, Chao; Li, Jianyong; Bewick, Patrick; Li, Qi; Zhao, Bingyu; Zhang, Bo (Frontiers in Plant Science, 2023)
The digestibility of soybean meal can be severely impacted by trypsin inhibitor (TI), one of the most abundant anti-nutritional factors present in soybean seeds. TI can restrain the function of trypsin, a critical enzyme that breaks down proteins in the digestive tract. Soybean accessions with low TI content have been identified. However, it is challenging to breed the low TI trait into elite cultivars due to a lack of molecular markers associated with low TI traits. We identified Kunitz trypsin inhibitor 1 (KTI1, Gm01g095000) and KTI3 (Gm08g341500) as two seed-specific TI genes. Mutant kti1 and kti3 alleles carrying small deletions or insertions within the gene open reading frames were created in the soybean cultivar Glycine max cv. Williams 82 (WM82) using the CRISPR/Cas9-mediated genome editing approach. The KTI content and TI activity both remarkably reduced in kti1/3 mutants compared to the WM82 seeds. There was no significant difference in terms of plant growth or maturity days of kti1/3 transgenic and WM82 plants in greenhouse condition. We further identified a T1 line, #5-26, that carried double homozygous kti1/3 mutant alleles, but not the Cas9 transgene. Based on the sequences of kti1/3 mutant alleles in #5-26, we developed markers to co-select for these mutant alleles by using a gel-electrophoresis-free method. The kti1/3 mutant soybean line and associated selection markers will assist in accelerating the introduction of low TI trait into elite soybean cultivars in the future.